Correction: Green catalytic conversion of bio-based sugars to 5-chloromethyl furfural in deep eutectic solvent, catalyzed by metal chlorides. Issue 40 (5th April 2016) - Zuo, Miao; Li, Zheng; Jiang, Yetao; Tang, Xing; Zeng, Xianhai; Sun, Yong; Lin, Lu
Abstract : Correction for 'Green catalytic conversion of bio-based sugars to 5-chloromethyl furfural in deep eutectic solvent, catalyzed by metal chlorides' by Miao Zuo et al., RSC Adv., 2016, 6, 27004–27007.